PENINGKATAN KOMPETENSI GURU DALAM PENGGUNAAN GOOGLE CLASSROOM MELALUI BIMLAT DI UPT SD NEGERI 346 GRESIK - Hodaifah (CENDEKIA: Jurnal Studi Keislaman, 2021)
The purpose of this study is to improve teacher competence in the use of Google Classroom through guidance and training (Bimlat) at UPT SD Negeri 346 Gresik. This type of research is school action research (action research). This research method is descriptive qualitative. The subjects of this study were 7 teachers consisting of 3 male teachers and 4 female teachers. This research was conducted from July to October 2020 in the 2020/2021 school year with 72 students. Based on the result of questionnaires and observation, these teachers are still not maximal in implementing Distance Learning (PJJ). The result of this study is an increase in teacher competence in using Google Classroom by 43%. In the first cycle from 14% to 57%. In the second cycle the competence of teachers in using Google Classroom increased by 14% from 57% to 71%. Students participation in creases by 10%. In the first cycle it was from 75% to 85% and in the second cycle it increased by 3% from 85% to 88%. Thus it can be concluded that the competence of teachers at UPT SD Negeri 346 Gresik has increased in the use of Google Classroom through guidance and training (Bimlat). In order for distance learning to be carried out well, it is necessary to have cooperation from all observers of education.